Anaerobic curable adhesive and container
A laminated film container with controlled oxygen permeability and specific adhesive components addresses premature curing in large capacity containers, ensuring stable storage and performance of anaerobic adhesives.
Patent Information
- Application Number
- JP2023106731
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Large capacity containers for anaerobic curable adhesives lead to reduced contact with air, causing premature curing due to oxygen cutoff, resulting in storage stability issues.
A soft plastic container made of laminated film with specific oxygen permeability and a spout, containing an adhesive with components (A) to (C), and optionally (D), which maintains anaerobic curing properties while suppressing physical property deterioration.
The solution ensures good storage stability and maintains adhesive performance even in large volumes, preventing premature curing and maintaining anaerobic curing properties during storage and transportation.
Smart Images

Figure 2025006131000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a container which does not affect the storage stability or physical properties of an anaerobic curing adhesive even when storing or transporting a large volume of the adhesive. [Background technology]
[0002] The curing of anaerobic curing adhesives is accelerated by blocking oxygen. (Patent Document 1) For this reason, for reasons of storage stability, measures such as intentionally sealing air in the container to allow contact with oxygen are taken. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Special Publication No. 2018-521155 Summary of the Invention [Problem to be solved by the invention]
[0004] However, when the container of the anaerobic curing sealing agent is made large, the contact area with the air (oxygen) decreases and the inside of the anaerobic curing adhesive is cut off from the air (oxygen), causing a storage stability problem in that curing begins from inside the anaerobic curing adhesive. [Means for solving the problem]
[0005] Means for Solving the Problems The inventors of the present invention conducted intensive research to solve the above problems, and as a result, discovered an anaerobic curing adhesive stored in a container that has good storage stability and that can suppress the effects on physical properties, even when the container is made large-capacity.
[0006] The gist of the present invention will now be described. [1] An adhesive comprising the following (A) to (C) contained in a soft plastic container made of a laminated film and having a pouring outlet. (A): A compound having one or more (meth)acryloyl groups in one molecule. (B): Anaerobic curing catalyst (C):Organic peroxide
[0007] [2] The oxygen permeability of the laminated film at 23°C is 100 cm 3 / (m 2 The adhesive described in [1] above has a resistance of 300 MPa (24h·atm) or higher.
[0008] [3] The adhesive according to [1] or [2], which is contained in the container at 20% or more by volume.
[0009] [4] The adhesive according to [1] or [2], wherein the container is an inner bag container of a bag-in-box.
[0010] [5] The adhesive according to [1] or [2], further comprising (D) a stabilizer.
[0011] [6] The adhesive according to [1] or [2], wherein the component (A) contains a polyfunctional (meth)acrylate monomer. Effect of the Invention
[0012] The present invention is extremely useful because it has good storage stability even when the container of an anaerobic curing adhesive is made large-capacity, and it can suppress deterioration in the performance of the anaerobic curing adhesive due to storage or transportation. [Brief description of the drawings]
[0013] [Figure 1] A side view of the spout side of the inner bag container of the present invention. [Diagram 2] A side view of the inner bag container of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The embodiments of the present invention will be described below. The present invention is not limited to the following embodiments. In this specification, "X to Y" means a range including the numerical values (X and Y) described before and after it as the lower and upper limits, and means "X or more and Y or less". In the present invention, a compound having a (meth)acryloyl group refers to a (meth)acrylate. The (meth)acryloyl group may have a (meth)acryloyl group in the form of a (meth)acryloyloxy group. In addition, the term "(meth)acryloyl" includes both acryloyl and methacryloyl. Thus, for example, the term "(meth)acryloyl group" includes both an acryloyl group (HC=CH-C(=O)-) and a methacryloyl group (HC=C(CH3)-C(=O)-). Similarly, the term "(meth)acrylate" includes both acrylate and methacrylate, the term "(meth)acryl" includes both acryl and methacryl, and the term "(meth)acrylamide" includes both acrylamide and methacrylamide.
[0015] The container of the present invention is a plastic inner container having a pouring outlet and made of a laminated film. The plastic constituting the laminated film is preferably a soft plastic from the viewpoint of storage stability. The soft plastic is a plastic having a modulus of elasticity of not more than 70 MPa in a bending test defined in JISK6900, or in a tensile test when the bending test is not applicable. Examples of types of plastic include acrylic, polystyrene, PET, polycarbonate, AS, vinyl chloride, polyethylene, polypropylene, polyacetal, ABS resin, phenolic resin, nylon, etc., and from the viewpoint of resistance to anaerobic curing adhesives and storage stability, PET, polyethylene, and polypropylene are preferred, polyethylene is more preferred, and it is most preferred that the plastic contains low-density polyethylene. The low-density polyethylene in the present invention refers to polyethylene having a density of less than 0.93.
[0016] In order to suppress anaerobic hardening, the container of the present invention has an oxygen transmission rate of 100 cm at 23°C. 3 / (m 2 ·24h·atm) or more is preferable, and 200cm 3 / (m 2 ·24h·atm) or higher is preferable, and 300cm 3 / (m 2 The oxygen permeability in the present invention is a value measured by gas chromatography based on JIS K 7126-1:2006.
[0017] From the viewpoint of adaptability to the transport environment, the container of the present invention is preferably used as an inner bag container of a bag-in-box. The bag-in-box is a packaging form consisting of an inner bag container for preventing leakage of the contents and a paper container or a plastic container for preventing the inner bag container from being broken due to an external impact.
[0018] The inner bag container is made of a polyolefin such as polyethylene or polypropylene, a monolayer of polyethylene and polyamide or a laminate of these, a laminate of polyethylene and ethylene-vinyl alcohol copolymer, a laminate of nylon and polyethylene, or a thermoplastic resin. Among these, polyethylene is particularly preferable in consideration of foldability, strength, etc. The polyethylene may be any of petroleum-derived polyethylene, plant-derived polyethylene, polyethylene obtained by mixing petroleum-derived polyethylene and plant-derived polyethylene in any ratio, and polyethylene obtained by laminating petroleum-derived polyethylene and plant-derived polyethylene. The inner bag container may be a molded container obtained by vacuum molding or blow molding a resin, or a bag obtained by heat-welding a film. Examples of bags obtained by heat-welding a film include gusset bags, flat bags, and standing pouches.
[0019] The shape of the container is not particularly limited, but from the viewpoint of ease of stacking during storage and transportation, it is preferably an approximately rectangular parallelepiped or approximately cubic shape, and most preferably an approximately cubic shape. From the viewpoint of storage stability of the anaerobic adhesive, the thickness of the laminated film is preferably 50 to 800 μm, and more preferably 100 to 500 μm.
[0020] The container of the present invention has a spout for storing and removing the adhesive. The material of the spout can be one that can be heat-sealed to the resin used in the laminated film, or one that can be fixed by a mounting means such as crimping a plastic ring member. From the viewpoint of storage stability and removal of the adhesive, the parts constituting the spout preferably do not contain metal, are preferably plastic, and are most preferably made of high-density polyethylene.
[0021] The container of the present invention contains an adhesive containing components (A), (B), and (C) described below. Since the adhesive containing components (A) to (C) has excellent anaerobic curing properties, as the volume increases, the contact area with oxygen in the air decreases, and the inside of the adhesive undergoes anaerobically curing. The volume that causes anaerobic curing in the present invention is 1 L or more. From the viewpoint of suppressing anaerobic curing, the volume of the anaerobic curing adhesive is preferably 80 volume % or less, more preferably 70 volume % or less, and most preferably 60 volume % or less, relative to 100 volume % of the container of the present invention. The lower limit is not particularly limited, but the effect of the packaging form of the present invention is remarkable when it is 20 volume % or more.
[0022] The component (A) used in the present invention is a compound having one or more (meth)acryloyl groups in one molecule, and is a main component constituting the adhesive of the present invention. Examples of the component (A) include oligomers and monomers having one or more (meth)acryloyl groups in one molecule. Here, the oligomer refers to a polymer in which two to several tens of monomer units (including monomer units other than (meth)acrylate monomers) are repeated. Examples of the types of oligomers having one or more (meth)acryloyl groups in one molecule in the present invention include urethane-modified (meth)acrylates and epoxy-modified (meth)acrylates.
[0023] The urethane-modified (meth)acrylate is a compound having a urethane bond in the main chain and a (meth)acryloyl group, which is formed by reacting an isocyanate group with a hydroxyl group. From the viewpoint of curability, the (meth)acryloyl group is preferably at the molecular chain end. Examples of a method for producing the urethane-modified (meth)acrylate include a method of reacting a polyol compound having a hydroxyl group with a (meth)acrylate having an isocyanate group, and a method of reacting a polyol compound having a hydroxyl group, a polyisocyanate compound, and a (meth)acrylate having a hydroxyl group.
[0024] The polyol compound having a hydroxyl group is not particularly limited, but examples thereof include polyesters. Polyols include terpolyols, polycarbonate polyols, and polyether polyols.
[0025] Examples of the (meth)acrylate having an isocyanate group include, but are not limited to, 2-methacryloyloxyethyl isocyanate, 2-isocyanatoethyl methacrylate, and 2-isocyanatoethyl acrylate.
[0026] Examples of the polyisocyanate compound include aromatic polyisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, tetramethylxylylene diisocyanate, diphenylmethane diisocyanate, naphthalene-1,5-diisocyanate, and triphenylmethane triisocyanate; isophorone diisocyanate, bis(4-isocyanate), and the like. alicyclic polyisocyanates such as 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, norbornane diisocyanate, and bicycloheptane triisocyanate; and linear or branched aliphatic polyisocyanates such as hexamethylene diisocyanate, 1,3,6-hexamethylene triisocyanate, and 1,6,11-undeca triisocyanate.
[0027] The (meth)acrylate having a hydroxyl group is not particularly limited, and examples thereof include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxycyclohexyl (meth)acrylate, 1,6-hexanediol mono(meth)acrylate, neopentyl glycol mono(meth)acrylate, (poly)ethylene glycol mono(meth)acrylate, (poly)propylene glycol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, etc. These may be used alone or in combination of two or more.
[0028] The epoxy-modified (meth)acrylate is a compound that can be synthesized by ring-opening polymerization of acrylic acid or the like with the glycidyl group of a glycidyl ether compound, but is not limited to this method. As the main chain of the glycidyl ether, those with various skeletons such as bisphenol A type, bisphenol F type, phenol novolac type, hydrogenated bisphenol A type, and hydrogenated bisphenol F type can be used. These may be used alone or in combination of two or more types.
[0029] Examples of the monomer having a (meth)acryloyl group include a monofunctional (meth)acrylate monomer having one (meth)acryloyl group in one molecule, and a polyfunctional (meth)acrylate monomer having two or more (meth)acryloyl groups in one molecule.
[0030] The monofunctional (meth)acrylate monomers include methoxydiethylene glycol mono(meth)acrylate, methoxytriethylene glycol mono(meth)acrylate, methoxytetraethylene glycol mono(meth)acrylate, methoxypentaethylene glycol mono(meth)acrylate, methoxyhexaethylene glycol mono(meth)acrylate, methoxyheptaethylene glycol mono(meth)acrylate, methoxyheptaethylene glycol mono(meth)acrylate, methoxyoctaethylene glycol mono(meth)acrylate, methoxynonaethylene glycol mono(meth)acrylate, methoxydecaethylene glycol mono(meth)acrylate, methoxytripropylene glycol mono(meth)acrylate, methoxytetrapropylene glycol mono(meth)acrylate, methoxypentapropylene glycol mono(meth)acrylate, methoxyhexapropylene glycol mono(meth)acrylate, methoxyheptapropylene glycol mono(meth)acrylate, methoxyheptapropylene glycol mono(meth)acrylate, methoxyhectapropylene glycol mono(meth)acrylate, Methoxyoctapropylene glycol mono(meth)acrylate, methoxynonapropylene glycol mono(meth)acrylate, methoxydecapropylene glycol mono(meth)acrylate, methoxytributylene glycol mono(meth)acrylate, methoxytetrabutylene glycol mono(meth)acrylate, methoxypentabtylene glycol mono(meth)acrylate, methoxyhexabtylene glycol mono(meth)acrylate, methoxyheptabtylene glycol mono(meth)acrylate, methoxyhexabtylene glycol mono(meth)acrylate Licorice mono(meth)acrylate, methoxyoctabutylene glycol mono(meth)acrylate, methoxynonabtylene glycol mono(meth)acrylate, methoxydecabutylene glycol mono(meth)acrylate, ethoxydiethylene glycol mono(meth)acrylate, ethoxytriethylene glycol mono(meth)acrylate, ethoxytetraethylene glycol mono(meth)acrylate, ethoxypentaethylene glycol mono(meth)acrylate, ethoxyhexaethylene glycol mono(meth)acrylate,Ethoxyheptaethylene glycol mono(meth)acrylate, ethoxyhexaethylene glycol mono(meth)acrylate, ethoxyoctaethylene glycol mono(meth)acrylate, ethoxynonaethylene glycol mono(meth)acrylate, ethoxydecaethylene glycol mono(meth)acrylate, ethoxytripropylene glycol mono(meth)acrylate, ethoxytetrapropylene glycol mono(meth)acrylate, ethoxypentapropylene glycol mono(meth)acrylate, ethoxyhexapropylene glycol mono(meth)acrylate, ethoxyheptapropylene glycol mono(meth)acrylate, ethoxyhexapropylene glycol mono(meth)acrylate, ethoxyoctapropylene glycol Examples of the acrylates include butyl glycol mono(meth)acrylate, ethoxy nonapropylene glycol mono(meth)acrylate, ethoxy decapropylene glycol mono(meth)acrylate, ethoxy tributylene glycol mono(meth)acrylate, ethoxy tetrabutylene glycol mono(meth)acrylate, ethoxy pentabtylene glycol mono(meth)acrylate, ethoxy hexabtylene glycol mono(meth)acrylate, ethoxy heptabtylene glycol mono(meth)acrylate, ethoxy hexabtylene glycol mono(meth)acrylate, ethoxy octabtylene glycol mono(meth)acrylate, ethoxy nonabutylene glycol mono(meth)acrylate, and ethoxy decabutylene glycol mono(meth)acrylate. These can be used alone or in combination of two or more.
[0031] Examples of polyfunctional (meth)acrylate monomers include tetrafunctional (meth)acrylate monomers such as ditrimethylolpropane tetra(meth)acrylate and pentaerythritol tetra(meth)acrylate; pentafunctional (meth)acrylate monomers such as dipentaerythritol monohydroxypenta(meth)acrylate and alkyl-modified dipentaerythritol penta(meth)acrylate; and hexafunctional (meth)acrylate monomers such as dipentaerythritol hexa(meth)acrylate.
[0032] The adhesive used in the present invention contains a polyfunctional (meth)acrylate monomer, but is not limited to this embodiment. By containing a polyfunctional (meth)acrylate monomer in the adhesive, the curability (reactivity) is improved, but the storage stability is reduced. However, by using the container of the present invention, the adhesive can be stably stored even if it contains a polyfunctional (meth)acrylate monomer. From the viewpoint of curability and storage stability, the content of the polyfunctional (meth)acrylate monomer is preferably 0.1 to 20 mass%, more preferably 1 to 10 mass%, and most preferably 2 to 7 mass% in 100 mass% of the (A) component.
[0033] The (B) component used in the present invention is an anaerobic curing catalyst. It is a main component for expressing the anaerobic curing property of the adhesive. The (B) component decomposes the (C) component described later in anaerobic conditions not in contact with oxygen to generate free radicals and promote curing. Examples of the (B) component include saccharin, amine compounds, azole compounds, mercaptan compounds, hydrazine compounds, and derivatives thereof, and these can be used alone or in combination. Among them, from the viewpoint of excellent anaerobic curing property, it is preferable to contain one or more compounds selected from the group consisting of saccharin, azole compounds, mercaptan compounds, and hydrazine compounds, more preferably to contain saccharin, and most preferably to combine saccharin, azole compounds, and mercaptan compounds. By combining multiple components, the anaerobic curing property is further improved compared to using them alone, and the container of the present invention can be used for stable storage.
[0034] Examples of the amine compound include heterocyclic secondary amines such as 1,2,3,4-tetrahydroquinoline and 1,2,3,4-tetrahydroquinaldine, etc.; heterocyclic tertiary amines such as quinoline, methylquinoline, quinaldine and quinoxalinephenazine, etc.; and aromatic tertiary amines such as N,N-dimethyl-anisidine and N,N-dimethylaniline, etc.
[0035] Examples of the azole compound include thiazole, isothiazole, thiadiazole, oxazole, isoxazole, oxadiazole, diazole, triazole, etc. More specific examples include saccharin, benzothiazole, 1,2,4-triazole, benzotriazole, hydroxybenzotriazole, benzoxazole, 1,2,3-benzothiadiazole, 3-mercaptobenzotriazole, etc.
[0036] Examples of the mercaptan compound include linear mercaptans such as n-dodecyl mercaptan, ethyl mercaptan, and butyl mercaptan, but are not limited to these.
[0037] Examples of the hydrazine compound include, but are not limited to, 1-acetyl-2-phenylhydrazine, 1-acetyl-2(p-tolyl)hydrazine, 1-benzoyl-2-phenylhydrazine, 1-(1',1',1'-trifluoro)acetyl-2-phenylhydrazine, 1,5-diphenyl-carbohydrazine, 1-formyl-2-phenylhydrazine, 1-acetyl-2-(p-bromophenyl)hydrazine, 1-acetyl-2-(p-nitrophenyl)hydrazine, 1-acetyl-2-(2'-phenylethylhydrazine), ethyl carbazate, p-nitrophenylhydrazine, and p-trisulfonylhydrazide.
[0038] From the viewpoint of anaerobic curability, the content of the (B) component is preferably 0.01 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and most preferably 1 to 5 parts by mass, relative to 100 parts by mass of the (A) component.
[0039] The component (C) used in the present invention is an organic peroxide. The component (C) is a main component for curing the anaerobic adhesive. Examples of the component (C) include hydroperoxides such as cumene hydroperoxide, t-butyl hydroperoxide, p-methane hydroperoxide, methyl ethyl ketone peroxide, cyclohexane peroxide, dicumyl peroxide, and diisopropylbenzene hydroperoxide, as well as ketone peroxides, diallyl peroxides, and peroxy esters. Among these, hydroperoxides are preferred from the viewpoint of excellent anaerobic curing properties and storage stability of the adhesive, and cumene hydroperoxide is more preferably used.
[0040] From the viewpoint of curability, the content of the (C) component is preferably 0.1 to 5 parts by mass, more preferably 0.3 to 3 parts by mass, and most preferably 0.5 to 2 parts by mass, per 100 parts by mass of the (A) component. The content of the (B) component is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, and most preferably 0.5 to 2 parts by mass, per 1 part by mass of the (C) component. By using an amount of 0.01 to 5 parts by mass, both anaerobic curability and storage stability can be achieved.
[0041] The adhesive of the present invention preferably further contains a stabilizer as component (D). Examples of component (D) include 2,6-di-t-butyl-4-methylphenol, hydroquinone, hydroquinone monomethyl ether, and 4-t-butylcatechol, with 2,6-di-t-butyl-4-methylphenol being preferred from the viewpoint of the storage stability of the adhesive.
[0042] The content of the component (D) is preferably from 0.01 to 0.5% by mass, more preferably from 0.02 to 0.3% by mass, and most preferably from 0.05 to 0.15% by mass, based on the total mass of the composition.
[0043] Furthermore, the adhesive of the present invention may further contain appropriate amounts of additives such as inorganic fillers, organic fillers, silane coupling agents, light stabilizers, photosensitizers, polymerization inhibitors, and chelating agents, provided that the adhesive properties are not impaired.
[0044] Examples of inorganic fillers include glass, silica, talc, alumina, mica, ceramics, silicone particles, calcium carbonate, aluminum nitride, carbon powder, kaolin clay, dried clay minerals, dried diatomaceous earth, etc. These may be used alone or in combination of two or more kinds.
[0045] The organic filler may be an organic powder composed of rubber, elastomer, plastic, polymer (or copolymer), etc. These may be used alone or in combination of two or more. Also, an organic filler having a multi-layer structure such as a core-shell type may be used. The average particle size of the organic filler is preferably in the range of 0.05 to 50 μm. From the viewpoint of improving the characteristics in a durability test, it is preferable to include a filler composed of a polymer or copolymer of an acrylic acid ester and / or a (meth)acrylic acid ester, or a filler composed of a polymer or copolymer of a styrene compound.
[0046] Examples of the silane coupling agent include glycidyl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldipropyloxysilane, 3-glycidoxypropyldimethylmonomethoxysilane, 3-glycidoxypropyldimethylmonoethoxysilane, 3-glycidoxypropyldimethylmonopropyloxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-glycidoxypropylmethyldiethoxysilane; vinyl group-containing silane coupling agents such as vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, and vinyltrimethoxysilane; 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropylmethyldipropyloxy ... Examples of the silane coupling agents include (meth)acrylic group-containing silane coupling agents such as propyl dimethyl monomethoxy silane, 3-methacryloxypropyl dimethyl monoethoxy silane, 3-acryloxypropyl methyl dipropyl oxy silane, 3-acryloxypropyl methyl dimethoxy silane, 3-acryloxypropyl methyl diethoxy silane, 3-acryloxypropyl methyl dipropyl oxy silane, 3-acryloxypropyl dimethyl monopropyl oxy silane, 3-acryloxypropyl dimethyl monomethoxy silane, 3-acryloxypropyl dimethyl monoethoxy silane, 3-acryloxypropyl dimethyl monopropyl oxy silane, and γ-methacryloxypropyl trimethoxy silane; amino group-containing silane coupling agents such as N-β-(aminoethyl)-γ-aminopropyl trimethoxy silane, γ-aminopropyl triethoxy silane, and N-phenyl-γ-aminopropyl trimethoxy silane; γ-mercaptopropyl trimethoxy silane; and γ-chloropropyl trimethoxy silane. It should be noted that the (meth)acrylic-containing silane coupling agent is not included in the component (A) of the present invention.
[0047] From the viewpoint of storage stability, the adhesive of the present invention preferably does not have moisture curing properties, and more preferably does not contain a metal as a component.
[0048] [Adhesive curing conditions] The adhesive that can be used in the present invention has a preferred curing temperature of 10 to 50°C, and more preferably 20 to 40°C. The curing time is not particularly limited, but is preferably 1 to 48 hours, and more preferably 6 to 24 hours. From the viewpoint of anaerobic curing, it is preferable to use the adhesive in contact with a metal during curing. The metal is not particularly limited, but examples include gold, silver, copper, iron, and nickel, and iron is preferred from the viewpoint of activating anaerobic curing.
[0049] [Transportation method] The adhesive stored in the container of the present invention has excellent stability during storage and transportation, and can be transported by various transportation methods, such as ships, freight cars, railroad cars, and airplanes. EXAMPLES
[0050] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0051] [Example 1, Comparative Examples 1 to 3] The following components were prepared to prepare the anaerobic curing adhesive contained in each container.
[0052] (A-1): urethane-modified (meth)acrylate 45 parts by mass (A-2): Epoxy-modified (meth)acrylate 20 parts by mass (A-3): 2-hydroxyethyl methacrylate 35 parts by mass (B-1): 1.5 parts by mass of saccharin (B-2): 0.4 parts by mass of benzothiazole (B-3): n-dodecyl mercaptan 0.3 parts by mass (C): 1 part by mass of cumene hydroperoxide (D): 0.1 parts by mass of 2,6-di-t-butyl-4-methylphenol
[0053] The components (A) and (D) were weighed into a mixing vessel, and the component (B) was added and mixed with a mixer for 30 minutes. The component (C) was then added and mixed for 10 minutes. All tests were carried out at 25°C. The specific gravity of the resulting adhesive at 25°C was measured using a specific gravity cup method and found to be 1.1.
[0054] (Reference example 1) 227 mL of the adhesive was sealed in a 370 mL plastic bottle made of low density polyethylene. Example 1 Oxygen permeability is 450cm 3 / (m 2 Two soft plastic containers with a volume of 18 L made of a laminated film of low-density polyethylene (pH 7.0-24h-atm) were prepared, and 5.5 L or 9.1 L of the adhesive was sealed in each of them. The sealed containers were placed in a paper container to form a bag-in-box package. Comparative Example 1 Two 18 L polypropylene plastic pails with lids were prepared, and 5.5 L and 9.1 L of the adhesive were placed in each pail. Comparative Example 2 Two plastic pails with lids and a volume of 18 L made of high density polyethylene were prepared, and 5.5 L and 9.1 L of the adhesive were filled into each pail. Comparative Example 3 A plastic tank made of high density polyethylene and having a volume of 18 L and two pouring outlets was prepared, and 5.5 L or 9.1 L of the adhesive was poured into each tank.
[0055] [Preservation test] Containers of each volume containing the adhesives of Reference Example 1, Example 1, and Comparative Examples 1 to 3 were left to stand in a thermostatic chamber at 40° C. for one month, and after returning to room temperature, the physical properties of the adhesives described below were evaluated.
[0056] [Set time] The adhesive was applied to the pin and inserted into the collar. The time (set time) until it could no longer be moved by hand was measured. The clearance during insertion was 0.01 mm. The results are summarized in Table 1. The set time is preferably less than 100 seconds. The pin is an iron pin with an outer diameter of 6φ×40 mm. The collar is an iron collar with an inner diameter of 6φ×15 mm that has been coated with a hardening accelerator and dried in advance. The hardening accelerator is a solution of 0.5 parts by mass of copper 2-ethylhexanoate in 100 parts by mass of acetone. When the adhesive of the present invention is used, the set time is preferably 7 seconds or less, and most preferably 5 seconds or less.
[0057] [Tensile shear adhesive strength] 0.1 g of a primer composition containing 100 parts by mass of acetone and 0.5 parts by mass of copper 2-ethylhexanoate is applied to a test piece of SPCC-SD having a width of 25 mm, a length of 100 mm, and a thickness of 0.3 mm, and then the test piece is left to dry at 25°C for 3 hours. Next, 0.1 g of adhesive is applied to the primer-treated test piece, and the other primer-treated test piece is overlapped so that the long side end is 10 mm long, and a weight of 100 g is placed on the bonding surface and fixed at 25°C for 24 hours to obtain an adhesive test piece. Next, the end of the adhesive test piece is pulled at a pulling speed of 50 mm / min with a universal tensile tester, and the tensile shear adhesive strength (MPa) is measured according to JIS K6850 (1999). When the adhesive of the present invention is used, the tensile shear adhesive strength is preferably 10 MPa or more, preferably 12 MPa or more, and most preferably 14 MPa or more.
[0058] [Table 1]
[0059] As shown in Table 1, it can be seen that Example 1, which uses the packaging material of the present invention, shows no deterioration in physical properties compared to the container of Reference Example 1. On the other hand, the container of Comparative Example 1 showed no deterioration in the setting time at 5.5 Lkg, but the setting time decreased significantly at 9.1 L. Also, a decrease in the shear adhesive strength was observed in all cases. The results showed that the adhesives stored using the containers of Comparative Examples 2 and 3 showed a significantly delayed setting time and a marked decrease in shear adhesive strength. Furthermore, when the relationship between storage containers and oxygen transmission rate was examined, the container of Example 1 showed an oxygen transmission rate of 450 cm 3 / (m 2 On the other hand, the oxygen permeability of the container of Comparative Example 1 was 88.8 cm 3 / (m 2 24h atm), and the oxygen permeability of the container of Comparative Example 3 was 16.3 cm 3 / (m 2 The oxygen permeability in the present invention was measured at 23°C using a gas chromatographic method in accordance with JIS K7126-1:2006. From the above, it can be seen that by using the container of Example 1, the adhesive can be stored stably without affecting its physical properties even when stored in a large volume. [Industrial Applicability]
[0060] The adhesive stored in the container of the present invention is extremely useful because, despite its anaerobic curing properties, it can be stably stored and transported even when stored and transported in large quantities without affecting the physical properties of the adhesive. [Explanation of symbols]
[0061] 1 bag-in-box inner bag container 2 spouts
Claims
1. An adhesive comprising the following (A) to (C) contained in a soft plastic container made of a laminated film and having a spout: (A): A compound having one or more (meth)acryloyl groups in one molecule (B): Anaerobic curing catalyst (C): Organic peroxide
2. The oxygen permeability of the laminated film at 23° C. is 100 cm 3 / (m 2 2. The adhesive stored in the container according to claim 1, wherein the adhesive has a viscosity of 100:1 or more.
3. 3. The adhesive according to claim 1, wherein the adhesive is contained in the container at 20% by volume or more.
4. 3. The adhesive according to claim 1, wherein the container is an inner bag container of a bag-in-box.
5. The adhesive according to claim 1 or 2, further comprising (D) a stabilizer.
6. The adhesive according to claim 1 or 2, wherein the component (A) contains a polyfunctional (meth)acrylate monomer.
Citation Information
Patent Citations
Anaerobic curable composition
JP2018521155A